Galectin-3 is linked to peripheral artery disease severity, and urinary excretion is associated with long-term mortality. (January 2022) - Ursli, Martin; Zierfuss, Bernhard; Grigassy, Thomas; Pesau, Gerfried; Koppensteiner, Renate; Schernthaner, Gerit-Holger; Höbaus, Clemens
Abstract: Background and aims: Galectin-3 (Gal-3) is a biomarker involved in fibrosis and vascular inflammation. Gal-3 has been linked to chronic kidney disease (CKD) and patients with peripheral artery disease (PAD). Conflicting reports exist about the relevance of Gal-3 in PAD. The study aims to elucidate a possible link between serum and urinary Gal-3 and long-term survival in PAD patients without critical limb ischemia and mild to moderate CKD. Methods: Galectin-3 (Gal-3) was measured in serum (n = 311) and urine (n = 266) of PAD patients (age 69 (62–77) years) by bead-based multiplex assay. Urinary Gal-3 concentration was normalized to urine creatinine (cr) levels. Mortality data were retrieved from the Austrian central death registry after a median observation period of 9.2 years. Survival analyses were performed by the Kaplan-Meier method and Cox-regression. Results: Serum Gal-3 was higher in patients with claudication symptoms ( p  = 0.001) and correlated inversely with the patients' ankle-brachial index ( R  = −0.168, p  = 0.009). Serum Gal-3 and urinary Gal-3 (uGal-3/cr) were associated with the estimated glomerular filtration rate ( R  = −0.359, p  < 0.001; R  = −0.285, p  < 0.001). Serum Gal-3 was not linked to all-cause mortality [HR 1.17 (CI 0.96–1.42)] over 9.2 years. However, uGal-3/cr was associated with all-cause mortality [HR 1.60 (CI 1.31–1.95)]. This association sustained multivariable adjustment for cardiovascular risk factors and renal function [HR 1.71 (CI 1.35–2.17)]. Conclusions: This study is the first to show an association of uGal-3/cr and long-term mortality in patients with PAD. Gal-3 was not predictive of long-term mortality but seems to be a marker of PAD severity in patients without critical limb ischemia. Graphical abstract: Image 1 Highlights: Elevated urinary Galectin-3 is associated with increased mortality in patients with peripheral artery disease (PAD). Serum Galectin-3 is not a predictor of survival in patients with PAD. Serum Galectin-3 is elevated in patients with claudication symptoms and those with reduced ankle-brachial index.